2011
DOI: 10.1017/s0950268811001890
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal risk factors for infantile pneumonia in a representative birth cohort

Abstract: Pneumonia is an important cause of mortality and morbidity in infants. However, information of risk factors for pneumonia in children aged <6 months is limited. This study aimed to evaluate the risk factors and their contribution to infantile pneumonia in a large population-based survey. Of 24,200 randomly sampled main caregivers invited, 21,248 (87.8%) participated in this study. A structured questionnaire was used to interview the main caregivers. Information regarding whether hospitalization was required, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 41 publications
1
37
1
Order By: Relevance
“…The association between maternal obesity and respiratory infections has been examined in two previous large cohort studies. Our results are consistent with findings from a Taiwanese study that reported an increased risk of pneumonia during the first 6 months for children of mothers with a pre-pregnancy BMI of 24 or higher 11. Additionally, a Norwegian study found an association between maternal obesity and lower respiratory infections during the first 18 months.…”
Section: Discussionsupporting
confidence: 92%
“…The association between maternal obesity and respiratory infections has been examined in two previous large cohort studies. Our results are consistent with findings from a Taiwanese study that reported an increased risk of pneumonia during the first 6 months for children of mothers with a pre-pregnancy BMI of 24 or higher 11. Additionally, a Norwegian study found an association between maternal obesity and lower respiratory infections during the first 18 months.…”
Section: Discussionsupporting
confidence: 92%
“…A second limitation is the potential for non-random loss to follow-up. Low birth weight [31] and prematurity [32] have been consistently found to be associated with risk of pneumonia among children in general, but we found no association. It is possible that these factors contributed to mortality before the first study visit and exclusion from this analysis.…”
Section: Discussioncontrasting
confidence: 89%
“…A high incidence of pneumonia (0.27 episodes per child-year (95% CI 0.23–0.32)) was reported in infants in the Drakenstein Child Health study, an African birth cohort study; maternal smoking was strongly associated with pneumonia (OR 2.36, 95% CI 1.45–3.82) [39]. Studies from Nepal and Indonesia confirm a similar risk [40,41], and in a large questionnaire-based study from Taiwan, prenatal ETS exposure or maternal smoking were significant risk factors for infantile pneumonia [42]. A Vietnamese study of almost 25,000 children less than 5 years of age found that household ETS exposure to be independently associated with hospitalization for pneumonia (adjusted OR 1.55, 95% CI 1.25–1.92) [43].…”
Section: Resultsmentioning
confidence: 89%